Amyotrophic Lateral Sclerosis (ALS) - A Case Report - Subaida, Fousiya Kunjumon; Sarju, Diya; Abdulkhadar, Binsha Malliyekal; Venugopal, Divya (Indian Journal of Pharmacy Practice)
This is a case of 54 year old male patient with Amyotropic Lateral Sclerosis. The patient is a known case of ALS. Patient came with features of quadriparesis of 1 year duration. Limb weakness started in each limb and slowly progressed to involve all four limbs. Patient also have difficulty in walking due to severe stiffness in both lower limb. Final diagnosis of MND-ALS was made because of limbs having both UMN and LMN signs which was confirmed by nerve conduction study and was treated with T. Riluzole 50 mg OD.
Keywords: Amyotropic Lateral Sclerosis (Als); Lmn And Umn Signs; Riluzole